Emotional and non-emotional pathways to impulsive behavior and addiction - Torres, Ana; Catena, Andrés; Megías, Alberto; Maldonado, Antonio; Cándido, Antonio; Verdejo-García, Antonio; Perales, José C. (Frontiers in Human Neuroscience, 2013)
Impulsivity is tightly linked to addiction. However, there are several pathways by means of which impulsive individuals are more prone to become addicts, or to suffer an addiction more intensely and for a longer period. One of those pathways involves an inadequate appraisal or regulation of positive and negative emotions, leading to lack of control over hazardous behaviors, and inappropriate decisions. In the present work, we assessed cocaine-dependent individuals (CDI; n=20), pathological gamblers (PG; n=21), and healthy controls (HC; n=23) in trait impulsivity measures (UPPS-P model’s dimensions), and decision-making tasks (Go/No-go; delay-discounting task). During the Go/No-go task, electroencephalographic (EEG) activity was recorded, and Go/No-go stimuli-evoked potentials (ERP) were extracted. Theory-driven ERP analyses focused on the No Go > Go difference in the N2 ERP. Our results show that negative urgency is one of the several psychological features that distinguish addicts from healthy controls. Nevertheless, among the measures of trait impulsivity, negative urgency is unique at independently covarying with gambling over-pathologization in the PG sample. Cocaine dependent individuals performed more poorly than gamblers in the Go/No-go task, and showed abnormal Go/no-go stimuli-evoked potentials. The difference between the No-go stimulus-evoked N2, and the Go one was attenuated by severity and intensity of chronic cocaine use. Emotional dimensions of impulsivity, however, did not influence go/No-go performance.